2013
DOI: 10.1016/j.pain.2013.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Emotional modulation of pain and spinal nociception in fibromyalgia

Abstract: Fibromyalgia (FM) is characterized by widespread pain, as well as affective disturbance (e.g., depression). Given that emotional processes are known to modulate pain, a disruption of emotion and emotional modulation of pain and nociception may contribute to FM. The present study used a well-validated affective picture-viewing paradigm to study emotional processing and emotional modulation of pain and spinal nociception. Participants were 18 individuals with FM, 18 individuals with rheumatoid arthritis (RA), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 80 publications
(123 reference statements)
8
93
0
Order By: Relevance
“…Of the included studies, 12 reported reflex threshold (Boureau et al, 1991;Coffin et al, 2004;De Marinis et al, 2007;Sterling et al, 2008;Courtney et al, 2009Courtney et al, , 2010Lim et al, 2012;Neziri et al, 2012;Rhudy et al, 2013;Smith et al, 2013Smith et al, , 2014Curatolo et al, 2015), six reported reflex peak magnitude or AUC or both Avramidis et al, 1998;De Marinis et al, 2007;Peddireddy et al, 2009;Rhudy et al, 2013;Kofler and Halder, 2014), six reported reflex latency (Avramidis et al, 1998;Katsarava et al, 2004;De Marinis et al, 2007;Courtney et al, 2009;Peddireddy et al, 2009;Kofler and Halder, 2014), and two reported reflex duration (Courtney et al, 2009;Peddireddy et al, 2009). Pain populations included 'chronic pain', migraine, migraine without aura, tension type headache, chronic tension type headache, fibromyalgia, rheumatoid arthritis, chronic upper back pain, chronic low back pain, knee osteoarthritis, chronic whiplash associated disorder, irritable bowel syndrome, chronic lateral epicondylalgia ('tennis elbow'), and a combination of idiopathic pain, myofascial pain, and headache (see Table 1 for study details).…”
Section: Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the included studies, 12 reported reflex threshold (Boureau et al, 1991;Coffin et al, 2004;De Marinis et al, 2007;Sterling et al, 2008;Courtney et al, 2009Courtney et al, , 2010Lim et al, 2012;Neziri et al, 2012;Rhudy et al, 2013;Smith et al, 2013Smith et al, , 2014Curatolo et al, 2015), six reported reflex peak magnitude or AUC or both Avramidis et al, 1998;De Marinis et al, 2007;Peddireddy et al, 2009;Rhudy et al, 2013;Kofler and Halder, 2014), six reported reflex latency (Avramidis et al, 1998;Katsarava et al, 2004;De Marinis et al, 2007;Courtney et al, 2009;Peddireddy et al, 2009;Kofler and Halder, 2014), and two reported reflex duration (Courtney et al, 2009;Peddireddy et al, 2009). Pain populations included 'chronic pain', migraine, migraine without aura, tension type headache, chronic tension type headache, fibromyalgia, rheumatoid arthritis, chronic upper back pain, chronic low back pain, knee osteoarthritis, chronic whiplash associated disorder, irritable bowel syndrome, chronic lateral epicondylalgia ('tennis elbow'), and a combination of idiopathic pain, myofascial pain, and headache (see Table 1 for study details).…”
Section: Included Studiesmentioning
confidence: 99%
“…Twelve studies (Boureau et al, 1991;Coffin et al, 2004;De Marinis et al, 2007;Sterling et al, 2008;Courtney et al, 2009Courtney et al, , 2010Lim et al, 2012;Neziri et al, 2012;Rhudy et al, 2013;Smith et al, 2013Smith et al, , 2014Curatolo et al, 2015) (pooled n = 1906) were included in reflex threshold comparisons. Two studies investigated two patient groups (Rhudy et al, 2013;Smith et al, 2013), which increased our group comparisons to 15.…”
Section: Reflex Thresholdmentioning
confidence: 99%
See 3 more Smart Citations